Purchase Behaviors During Emergencies: Exploratory Analyses and Predictive Models - Kayhan, Varol O.; Trocchia, Philip J.; Watkins, Alison (Journal of Applied Business and Economics, 2022)
In this study, we distinguish between traditional emergency events (i.e., those that occur frequently) and novel emergency events (i.e., those that occur rarely in one’s lifetime). We examine consumers’ shopping behaviors during both types of emergency events. Using data from a U.S. supermarket chain, we answer three research questions. First, we conduct multiple cluster analyses and identify three distinct shopping behaviors during emergency events, namely strategic, routine, and stocking. Second, we examine how consumers change their shopping behaviors toward novel emergency events and find that majority of consumers continue to engage in routine shopping behaviors. Third, we examine how to predict shopping behaviors before emergency events and show that all three types of shopping behaviors can be predicted with reasonable levels of accuracy based on consumers’ spending before emergency events.